Successful business intelligence : unlock the value of BI & big data - Howson, Cindi (New York : McGraw-Hill Education, 2014)
Expanded to cover the latest in business intelligence-big data, cloud, mobile, visual data discovery, and in-memory-this fully updated bestseller by BI guru Cindi Howson provides the most modern techniques to exploit BI for the highest ROI.
Includes bibliographical references (pages 299-308) and index.
Keywords: Business intelligence